Strategy for Improving Students' Literacy Skills at SB At-Tanzil Putra Kajang, Malaysia - Fina Dwi Agustina; Tasti Septiviani Ivana Ika Putri; Arizqi Ihsan Pratama (Beginner: Journal of Teaching and Education Management, 2025)
Darunnajah University's International Community Service Program (KKN) aims to improve literacy in Malaysia. Through the theme "Strategy to Improve Students' Literacy Skills at SB At-Tanzil Putra Kajang, Malaysia," this activity combines interactive teaching, character education, and literacy development. Participatory methods are applied, involving teachers, parents, and the local community, to ensure the sustainability of the program. The results reflect an increase in students' literacy and character skills, with a balance between faith and technology as the main focus. This program emphasizes the importance of holistic education to produce a superior and globally competitive generation, while strengthening bilateral relations in the field of education.